Construction of recombinant Saccharomyces cerevisiae strains containing endo-1,4-β-glucanase gene of Aspergillus niger into the chromosomal HO locus (Experimental biology, 2015)
The vector carrying a selective marker gene resistant to geneticin (G418), a constitutive promoter and terminator ofyeast gene glyceraldehyde 3-phosphate dehydrogenase (GAPDH) was created for integration of genetic material into the chromosomal HO locus. Through the use of a genomic integration vector, new yeast strains with efficientexpression of endo-1,4-â-glucanase of the fungus Aspergillus niger were obtained. Approaches used in this study has been shown to be perspective in the development of industrial strains for the fermentation of cellulose-containing materials.
Keywords: cellobiohydrolase; endo-1; 4-â-glucanase; Saccharomyces cerevisiae; gene expression; enzymatic activity; glycosylation